Preservation And Conservation Of Archaeological Sites And Artefacts In Malaysia. - Chia, Dr. Stephen (Universiti Sains Malaysia, 2003)

(untitled)
Archaeological sites and artefacts are among the most vulnerable of human cultural heritage that have suffered extensive damages. Excavations of archaeological sites and the removal of artefacts from sites have often caused abrupt changes to their ambient preserving conditions.